Pemicuan Sanitasi Total Berbasis Masyarakat (STBM) Pilar BABS di Kota Sibolga - Rapotan Hasibuan; Susilawati Susilawati; Meutia Nanda (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2021)
Community Led Total Sanitation (CLTS) coverage in Sibolga city is still relatively low. This article aims to reconstruct the residents' understanding of the pillars of open defecation free (ODF) in Huta Tonga-Tonga Village, North Sibolga District. This activity is important to do in connection with the results of environmental observations and interviews with residents and health workers which highlight the understanding of personal hygiene and regional geographic conditions as the main obstacles. The socialization method was used in this work were lecturing in the form of counseling, measuring the volume of feces, compiling a flowchart of contamination by residents. The extension method is equipped with making BABS mapping, proper handwashing, and discussion of questions and answers with content of triggering elements. The resulting output is in the form of increased understanding of the importance of changing the behavior of open defecation and awareness of the potential diseases it can cause. In addition, the output can also be seen from the ability of residents to compile a fecal contamination flowchart. The follow-up of this activity is that the Health Office, the Sub-district side, the Puskesmas, and the Village Head should monitor and evaluate the results of the STBM triggering until finally the Huta Tonga-Tonga Village actually becomes a ODF Village.